(untitled) (International journal of artificial intelligence, 2026)
This article examines the essence and content of the technology for developing the design of a modern preschool educational institution. The study analyzes the regulatory and legal foundations of preschool design, conceptual planning, modeling of the educational environment, as well as the integration of pedagogical and technical solutions. Particular attention is paid to the principles of creating a safe, developmental, and inclusive educational environment that takes into account children’s age-specific and individual characteristics. The research findings have practical significance for designing preschool educational institutions based on modern pedagogical approaches.